Serum level of progranulin in patients with psoriasis and its relation to disease severity - Reham M Abdel Gaber; Rasha M Hefny; Taghreed M Kamal El Din; Rehab S Sotohy; Sahar I Abdel Moez (Wolters Kluwer Medknow Publications, 2020)
Background Studies have identified progranulin (PGRN) as a proinflammatory and anti-inflammatory protein. Data from other several inflammatory diseases suggest the role of this adipokine in psoriatic pathophysiology. Objective The aim was to investigate serum levels of PGRN in patients with psoriasis compared with healthy controls, and to consider their relation to disease duration, disease severity, and obesity markers. Patients and methods Serum PGRN concentrations were measured in 37 patients with active plaque-type psoriasis and 25 healthy controls by using specific enzyme-linked immunosorbent assays. Results Patients with psoriasis showed higher levels of serum PGRN compared with healthy controls (P<0.033). Concentrations of serum PGRN showed significant positive correlation with Psoriasis Area and Severity Index score, BMI, and waist circumference (P<0.001). Conclusion Serum PGRN could be a useful biomarker of psoriasis severity and could be a potential target for new therapies for psoriasis.